OCCURRENCE OF FIBROMA IN A MAJOR CARP, LABEO ROHITA - Pillai, C Thankappan; Thampy, D M (Indian Journal of Fisheries, 2011)
A case of fibroma in a juvenile specimen of the Indian major carp Lebeo rokila is discussed. Aquaculturc becomes a viable practice only when the problems of disease and associated mass mortalities are brought down. Of all the fish diseases, the problems of those connected with neoplastic diseases are yet to be explored. Fishes form useful animal models to study the effect of carcinogens in body systems. So a survey and analysis of fish neoplasms are often helpful in indicating human carcinogens when especially many neoplastic diseases of humans remain unresolved.